STRATEGI PENINGKATAN KINERJA PEGAWAI PADA PT GOTHRU MEDIA INDONESIA MENGGUNAKAN METODE SIX SIGMA - Supriatna, Nano; Franciskus Antonius Alijoyo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
In an era of increasingly tight business competition, improving employee performance is crucial for the success of a company. One method that is being pursued to improve the quality and efficiency of business processes is the Six Sigma Method. The aim of this research is to explore and understand strategies for improving employee performance at PT Gothru Media Indonesia using the Six Sigma Method. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the Six Sigma method can be used to improve employee performance at PT. Gothru Media Indonesia. Strategies that can be used include problem identification and definition, data measurement and analysis, solution development, solution implementation and monitoring and control. The application of the Six Sigma method needs to be carried out systematically and continuously to achieve optimal results.